High throughput biodiesel production from waste cooking oil over metal oxide binded with Fe2O3 - Snunkhaem Echaroj; Nattadon Pannucharoenwong; Keyoon Duanguppama; Phadungsak Rattanadecho; Suwipong Hemathulin (Energy Reports, 2023)
This research investigated the effects of magnetic metal oxide catalysts and operating parameters on the transesterification of waste cooking oil to biodiesel in a continuous reaction setup. Ferric oxide (Fe2O3) was incorporated in alkaline oxide to provide magnetic characteristics, instead of using filters to capture catalysts within the heating zone. Biodiesel production was conducted in a packed glass tubular reactor under ultrasonication in a water bath. The reaction parameters included reaction temperature, amount of catalyst, residence time, and ultrasonic power. Three different catalysts were studied, including calcium oxide on Fe2O3, zinc oxide on Fe2O3, and magnesium oxide on Fe2O3. The results revealed that the biodiesel yield increased with increasing reaction temperature, amount of catalyst, residence time, and ultrasonic power. The optimized biodiesel yield of 94.3% was produced over calcium on Fe2O3 at 65 °C, the methanol-to-oil ratio of 11:1, the residence time of 6.2 min, and the ultrasonic power of 185 W. An increase of reaction temperature to 75 °C resulted in a decline in biodiesel yield to 91.3% due to methanol evaporation at higher temperatures. The catalytic stability was also tested at 60 °C, 6 wt% catalyst, and 185 W ultrasonic power. It was revealed that calcium oxide on Fe2O3 catalyst demonstrated superior catalytic stability with a biodiesel yield decrease of only 10% after 34 days on stream. This suggested the magnetic feature of the catalyst helped prevent leakage of the catalyst from the system. Moreover, the quality of biodiesel met the ASTM D6751 standard for transportation fuel.